Faktor-Faktor yang Mempengaruhi Produksi Kakao di Kecamatan Semadam Kabupaten Aceh Tenggara - Jannus Roberto; Rika Fitri Ilvira (Departemen Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala associated with AAI (Asosiasi Agribisnis Indonesia). Jl. Tgk. Hasan Krueng Kalee No. 3, Kopelma Darussalam, Banda Aceh, 23111, Indonesia. Email: agrisep@usk.ac.id, 2026)
This study aims to analyze the factors that influence cocoa production in Semadam District, Southeast Aceh Regency. Cocoa is one of the mainstays of the plantation sector that plays an important role in the economy, especially in Southeast Aceh Regency which is the largest cocoa producing area in Aceh Province. However, there is a fluctuation in production from year to year which indicates the need for a study of production factors. Data were obtained from 38 cocoa farmer respondents selected by purposive sampling. The analysis method used is the Cobb-Douglas production function, with independent variables including land area, labor, seeds, fertilizers, and pesticides, and the dependent variable is cocoa production. The results of the study showed that simultaneously all variables had a significant effect on cocoa production. Partially, the variables of land area, seeds, and fertilizers had a positive and significant effect, while labor and pesticides did not have a significant effect. The coefficient of determination (R²) of 0.948 indicates that 94.8% of the variation in cocoa production can be explained by the five variables. This study recommends increasing the efficiency of the use of production inputs to optimize cocoa yields.